Urgensi Penerapan Keselamatan dan Kesehatan Kerja Pada Organisasi Publik di Kabupten Jember - Khanifatul Khusna; Abdul Muhsyi; Naulus Saádah; Santi Berliana C (Faculty of Social and Political Science, 2023)
The implementation of Occupational Safety and Health (K3) is necessary for employees who work in high-risk environments. This study aims to describe the implementation of K3 at PT PLN (Persero) ULP Jember and Pos Indonesia Jember. This research uses descriptive qualitative method. Research findings obtained from literature reviews. The study found that the K3 implementation in both locations was well-executed, following the proper stages for K3 implementation. The research recommends to increase physical facilities.